2007
DOI: 10.1353/csd.2007.0054
|View full text |Cite
|
Sign up to set email alerts
|

Examining Sense of Belonging Among First-Year Undergraduates From Different Racial/Ethnic Groups

Abstract: This study examined sense of belonging among a national sample of 2,967 first-year students. Guided by the work of Hurtado and Carter (1997), relationships between several aspects of the college environment and sense of belonging were examined. Findings indicated that African American, Hispanic/Latino, and Asian Pacific American students reported a less strong sense of belonging than White/Caucasian students. The social dimensions of the transition to college and residence hall climate and perceptions of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
345
2
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 434 publications
(380 citation statements)
references
References 22 publications
24
345
2
9
Order By: Relevance
“…First, sense of belonging was measured with a six-item scale developed for the present study. The fact that we found no differences between ethnic minority and majority students' sense of belonging (see Table 2), contrary to previous research (Hurtado 1994;Hurtado and Carter 1997;Johnson et al 2007;Read et al 2003;Zepke and Leach 2005), makes us wonder if the scale was appropriate. It is possible that the concept of sense of belonging is more complex than we assumed.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…First, sense of belonging was measured with a six-item scale developed for the present study. The fact that we found no differences between ethnic minority and majority students' sense of belonging (see Table 2), contrary to previous research (Hurtado 1994;Hurtado and Carter 1997;Johnson et al 2007;Read et al 2003;Zepke and Leach 2005), makes us wonder if the scale was appropriate. It is possible that the concept of sense of belonging is more complex than we assumed.…”
Section: Discussioncontrasting
confidence: 98%
“…For example, various US studies demonstrated that African American students and Asian Pacific or Hispanic/Latino students feel less strongly that they belong in a program than white American students (Hurtado and Carter 1997;Johnson et al 2007). In another study, Hurtado (1994) found that many Hispanic students feel that they do not 'fit in' on their campus.…”
Section: Sense Of Belongingmentioning
confidence: 99%
See 1 more Smart Citation
“…En educación, existe algún análisis sobre la relación de los estudiantes con sus centros educativos y su posible impacto en el rendimiento académico y la motivación (véase Johnson et al, 2007). El estudio de la construcción de la identidad profesional en los estudiantes es prácticamente inexistente en el campo de las artes; los autores únicamente conocen el trabajo de D´Santiago Tiburcio y Gutiérrez Rico (2014).…”
Section: Consideraciones Preliminaresunclassified
“…Without the assistance of Hispanic faculty and staff to serve as mentors and advisors, their experiences were hardly understood and solved. Moreover, the college environment has proven to impact students' sense of belonging (Johnson et al, 2007). Johnson and his colleagues found that Hispanic students perceived a lower sense of belonging in institutions than Caucasian students.…”
Section: Hispanic Students In Higher Educationmentioning
confidence: 99%